Correcting the linear and nonlinear distortions for atomically resolved STEM spectrum and diffraction imaging. (29th January 2018) - Wang, Yi; Suyolcu, Y Eren; Salzberger, Ute; Hahn, Kersten; Srot, Vesna; Sigle, Wilfried; van Aken, Peter A
Abstract : We report a software tool for post-correcting the linear and nonlinear image distortions of atomically resolved 3D spectrum imaging as well as 4D diffraction imaging. This tool improves the interpretability of distorted scanning transmission electron microscopy spectrum/diffraction imaging data. Abstract: Specimen and stage drift as well as scan distortions can lead to a mismatch between true and desired electron probe positions in scanning transmission electron microscopy (STEM) which can result in both linear and nonlinear distortions in the subsequent experimental images. This problem is intensified in STEM spectrum and diffraction imaging techniques owing to the extended dwell times (pixel exposure time) as compared to conventional STEM imaging. As a consequence, these image distortions become more severe in STEM spectrum/diffraction imaging. This becomes visible as expansion, compression and/or shearing of the crystal lattice, and can even prohibit atomic resolution and thus limits the interpretability of the results. Here, we report a software tool for post-correcting the linear and nonlinear image distortions of atomically resolved 3D spectrum imaging as well as 4D diffraction imaging. This tool improves the interpretability of distorted STEM spectrum/diffraction imaging data.